Socio-psychological factors in the menopausal experience of selected middle class Filipino women - Abrenica, Alexa P. (Animo Repository, 1994)
This study describes the menopausal experience and coping strategies of Filipino women.The menopausal experience was investigated in the light of civil and employment status, menopausal phase, life satisfaction, and life events. This was done to map out a counseling model appropriate for the Filipino mid-life.The descriptive method was used. The interview and ginabayang talakayang were utilized for data gathering. Ginabayang talakayan was an indigenous group research method which emphasizes equality of status among participants, facilitator, and process observer. This can be seen in the sharing of ideas and experiences according to a set of guide questions which participants formulate. This equality of status was also made evident in the involvement of the participants in the interpretation of the data generated. Sixty-three purposively-selected women participated in the study. The criteria for selection were: (a) age (40-60) (b) menopausal phase (from pre-menopausal to post-menopausal) (c) employment status (working and non-working) and (d) civil status (single, married, widowed, and separated). Fifty-three women were interviewed. Five nuns and 5 grade school teachers participated in the two ginabayang talakayan sessions.An interview guide, which included the 5-point scale Kaufert-Syrotuik Symptom Index (KSSI) and the Bulatao Happiness Scale, was used to gather the data. A separate set of guide questions was utilized for the ginabayang talakayan. Data from interview and ginabayang talakayan were content analyzed, categorized, tabulated and converted into percentages.Results showed that menopausal experience was highly personal. It varied from one woman to another in terms of intensity and type and number of symptoms experienced. Some discernible patterns seen were: a) married women experienced most number of symptoms b) the employed noted more symptoms as seen in the KSSI and c) the pre-menopausal encountered the most number of symptoms. Common reported symptoms were hot flashes, fatigue, headaches, and vaginal dryness. Irritability and depression were the predominantly experienced symptoms. The changes experienced were not limited to those in the KSSI list.A counseling model, consisting of menopausal education and crisis counseling as primary and tertiary interventions respectively, was proposed in response to the subjects' endorsement of the necessary interventions.It was concluded that though menopausal experience of the women under study followed a particular pattern, changes varied from woman to woman. Menopause was not a significant event and was viewed simply as a natural milestone. The use of minimizing personal discomfort strategies enabled the women to cope with changes. Life events were viewed independently of menopause. Increased awareness of the changes could contribute to an adequate coping with menopause.Life satisfaction was neither a function of civil status nor menopausal phase. Education and socio-economic status were the significant factors in life satisfaction.